Deploying Creative Thinking to Strengthen Entrepreneurial Capability Among University Students in Nigeria - Aboluwodi, Akinjide (Journal of Education and Research, 2018)
Most of the students studying entrepreneurship in Nigerian universities lack entrepreneurial capability- that is, they lack the freedom to pursue and achieve entrepreneurial opportunity. Freedom is seen here in terms of those conditions that must be in place for students to be able to carry out their entrepreneurship studies. These are conditions that support the well-being of the students and may be seen as having good shelter, being well nourished, being healthy, being able to do their normal studies among others. The paper examined why the presence of these conditions is likely to assist students to improve their creative thinking and strengthen their entrepreneurial capability. It explored Amartya Sen’s Capability Approach, focusing on freedom, opportunities, and functionings to explain the required favourable conditions that make learning worthwhile for students, and how it accounts for students’ ability to strengthen their entrepreneurial capability. The paper argued for the deployment of creative thinking to strengthen entrepreneurial capability among students of entrepreneurship in universities in Nigeria. It concluded by urging universities in Nigeria to adopt relevant curriculum in addition to providing students with a decent learning environment to enable them to develop creative thinking that could be used in entrepreneurship education.